2017
DOI: 10.3126/jcmc.v6i1.16575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on pulmonary function tests: A comparative study between athletes and non-athletes in Nepalese settings

Abstract: Due to regular exercises, athletes tend to have an increase in pulmonary functions when compared to non exercising individuals, especially when the exercise is strenuous. Intensity and severity of sports engaged in by the athletes determines the extent of strengthening of the inspiratory muscles with a resultant increase in the lung volumes and capacities. Pulmonary parameters like tidal volume and forced vital capacity are significantly higher in athletes than in non athletes. A cross sectional comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Our study also supports the previous studies which stated that regular long-term physical exercises help improve the strength of respiratory muscles [11], while good physical tness is associated with better respiratory function [12]. Therefore, participation in certain physical activities or sports may lead to the strengthening of respiratory muscles, improvements in pulmonary functions, and achieving an effective pulmonary function (FVC, FEV1) [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…Our study also supports the previous studies which stated that regular long-term physical exercises help improve the strength of respiratory muscles [11], while good physical tness is associated with better respiratory function [12]. Therefore, participation in certain physical activities or sports may lead to the strengthening of respiratory muscles, improvements in pulmonary functions, and achieving an effective pulmonary function (FVC, FEV1) [13,14].…”
Section: Discussionsupporting
confidence: 90%
“…7 The FEV1/FVC ratio is used as a marker for obstructive and restrictive conditions of the lungs. 18 The mean FEV1/FVC in athletes (105.95%) was significantly higher compared to that of non-athletes (102.69%; P=0.011), similar to results from Vedala et al 17 However, Akhade et al found no significant difference in mean FEV1/FVC percentage between athletes and non-athletes. 19 Regarding the FEF of 25-75%, we found no statistically significant differences between athletes and non-athletes.…”
Section: Discussionsupporting
confidence: 78%
“…16 We found that the mean FVC in athletes was significantly better (95.66%) compared to that of non-athletes (88.43%). Similarly, Vedala et al 17 and Mahotra 18 stated that the FVC in athletes was significantly higher than in non-athletes. Muscular exercise increases the rate and depth of respiration and improves FVC, the consumption of O 2 , and the rate of diffusion.…”
Section: Discussionmentioning
confidence: 91%
“…Lazovic et al (2015) reported that respiratory adaptations occurred with participation in sports activities and these adaptations changed according to the type of activity [16]. Therefore, participation in certain physical activities or sports may lead to the strengthening of respiratory muscles, improvements in pulmonary functions, and achieving an effective pulmonary function (FVC, FEV 1 ) [17]. In addition, it has been reported that aerobic power is positively associated with lung volumes and it has been reported that lung volumes and capacities increase with participation in sportive activities at early ages [14,28].…”
Section: Discussionmentioning
confidence: 99%